The physical-chemical concept of matter in Latin American Primary Schools: When and how much is done - Atrio Cerezo, Santiago; Calvo Pascual, M. Araceli (Education Policy Analysis Archives, 2017)
This paper seeks to identify when and how thoroughly Latin American primary education systems deal with concepts of “matter.” First, an analysis of their presence in the official curricula of 10 Latin American countries is made, as well as the problems identified by experts from different countries. Second, the results of the exploitation of data from the Second Regional Comparative and Explanatory Study (SERCE), developed by UNESCO, are shown. The study concludes that concepts of “matter” are present in the aforementioned curricula and in the classrooms of the 10 countries analyzed, although there are a number of differences between those countries. The importance of Science Education in teacher training is evidenced by the fact that the didactic resources and the methodology used by teachers in the classrooms will determine how science-based content is learnt. This methodology should consider students’ sociocultural context, balancing time dedicated to teaching whether in urban and rural schools or in state and public schools.